Effects of incubation time and filtration method on Kd of indigenous selenium and iodine in temperate soils. (October 2017) - Almahayni, T.; Bailey, E.; Crout, N.M.J.; Shaw, G.
Abstract: In this study, the effects of incubation time and the method of soil solution extraction and filtration on the empirical distribution coefficient ( K d ) obtained by de-sorbing indigenous selenium (Se) and iodine (I) from arable and woodland soils under temperate conditions were investigated. Incubation time had a significant soil- and element-dependent effect on the K d values, which tended to decrease with the incubation time. Generally, a four-week period was sufficient for the desorption K d value to stabilise. Concurrent solubilisation of soil organic matter (OM) and release of organically-bound Se and I was probably responsible for the observed decrease in K d with time. This contrasts with the conventional view of OM as a sink for Se and I in soils. Selenium and I K d values were not significantly affected by the method of soil solution extraction and filtration. The results suggest that incubation time is a key criterion when selecting Se and I K d values from the literature for risk assessments. Values derived from desorption of indigenous soil Se and I might be most appropriate for long-term assessments since they reflect the quasi-equilibrium state of their partitioning in soils. Highlights: Desorption K d of indigenous Se and I were determined in temperate soils. Desorption K d values were typically higher than those from sorption experiments. Soil type and incubation time had an overall significant effect on K d . The method of soil solution extraction and filtration had a limited effect on K d .